La cosa juzgada fraudulenta y el derecho a la verdad que tiene la víctima - Román Melo, Álvaro Sebastián (2018)
In the present work emphasis has been made, firstly, on giving a legal, doctrinal and, if possible personal, conceptualization of what res judicata means; in a second moment, the elements of the res judicata are analyzed and how, due to the non-observance of some of them, there are errors in judgments that are already final and res judicata, which leads to fraudulent res judicata, which is not contemplated in the Ecuadorian legislation. However, there are precedents in our country (Ecuador) regarding the reopening of a case because the fraudulent res judicata has been configured. Subsequently, the term “victim” is analyzed; the rights they have as such; and, the criminal procedural guarantees as instruments that make viable their After a relationship is made between the right to truth and fraudulent res judicata, which triggers the analysis of the process called “Gonzales and others” also known as “Fybeca”, for being the first case in our country in which the principles of due process, legal security and consequently the right to the truth of the victims were affected. In the same way in the present work, a dogmatic and jurisprudential analysis of the case “Gonzales and others” is carried out to finalize in the conclusions that were reached after having investigated the main theme of this essay.